The sales–marketing integration gap: a social identity approach. Issue 4 (2nd October 2018) - Sleep, Stefan; Lam, Son K.; Hulland, John
Abstract : Firms often promote integration between sales and marketing functions. However, research has mostly focused on improving the level of realized integration and ignored the integration gap, defined as managers' perceptions of the difference between realized and desired integration. Using the social identity approach, this study examines three potential antecedents of this integration gap, with sales–marketing task interdependence as the boundary condition. Results from a multifirm survey of 196 sales and marketing managers show that the joint effect between task interdependence and competitor orientation on the integration gap is opposite that of task interdependence and customer orientation. In addition, the authors find that regardless of task interdependence, rewards that focus solely on either sales or marketing widen the integration gap. They also find a negative relationship between the integration gap and firm performance. Our study informs managers of various ways to narrow the sales–marketing integration gap.